Numerical investigation of hydrodynamic performance of conventional and ducted propellers - Tarafder, Md Shahjada; Md Imdadul Haque,; Asaduzzaman, Md; Laku, Md Zahidul Islam (Journal of Naval Architecture and Marine Engineering, 2023)
An efficient and optimized propeller can reduce ship operating costs substantially. The recent development of Computational Fluid Dynamics (CFD) has a significant impact on the initial stage of propeller design. Being motivated by the success of a CFD approach known as Reynolds Averaged Navier-Stokes Equation (RANSE) in solving many hydrodynamic problems, this paper explores the use of RANSE solver to estimate propeller open water characteristics. Multiple RANSE solvers can be used for CFD simulation. Among these k-ϵ turbulence model is used for its better performance on propeller analysis. Numerical results are compared with the results obtained from well-established polynomial regression formulae of Wageningen-B series propeller. A comparison shows an error of less than 5% for most of the cases. The same propeller is numerically analyzed again after fitting a 19A duct on it. To achieve optimal performance space between the duct and propeller blade tip is kept as small as possible. Grid independence test is done in both cases for a more accurate estimation within a particular time frame. Mesh sensitivity analysis is carried out in this paper based on thrust and torque coefficients. This paper shows that the maximum computed efficiencies for both the conventional and ducted propeller systems are found to be 60% but at different speeds. The ducted propeller system gives better performance up to advance coefficient J=0.48. Journal of Naval Architecture and Marine Engineering, 20(3), 1–10